A short review about the Bethe-Salpeter equation and the solution of the χ2φ model in minkowski space - Gigante, Vitor; Gutierrez, C. [UNESP]; Nogueira, J. H. Alvarenga; Ydrefors, E. (My University, 2016)
We present a brief review of the Bethe-Salpeter equation including a list of references with which the reader can undertake deeper studies of the subject. We also present some recent results for the χ2φ model solving the Bethe-Salpeter equation with the light-front projection and the Nakanishi integral representation of the Bethe-Salpeter amplitude.